Long-term postoperative quality of life in childhood survivors with cerebellar mutism syndrome - Zhu, Kaiyi; Yang, Wei; Ying, Zesheng; Cai, Yingjie; Peng, XiaoJiao; Zhang, Nijia; Sun, Hailang; Ji, Yuanqi; Ge, Ming (Frontiers in Psychology, 2023)
Background: To investigate the long-term quality of life (QoL) of children with cerebellar mutism syndrome (CMS) and explore the risk factors for a low QoL. Procedure: This cross-sectional study investigated children who underwent posterior fossa surgery using an online Pediatric Quality of Life Inventory questionnaire. CMS and non-CMS patients were included to identify QoL predictors. Results Sixty-nine patients were included (male, 62.3%), 22 of whom had CMS. The mean follow-up time was 45.2 months. Children with CMS had a significantly lower mean QoL score (65.3 vs. 83.7, p < 0.001) and subdomain mean scores (physical; 57.8 vs. 85.3, p<0.001; social: 69.5 vs. 85.1, p=0.001; academic: p = 0.001) than those without CMS, except for the emotional domain (78.0 vs. 83.7, p = 0.062). Multivariable analysis revealed that CMS (coefficient= -14.748.61, p = 0.043), chemotherapy (coefficient= -7.629.82, p = 0.013), ventriculoperitoneal (VP) shunt placement (coefficient= -10.14, p = 0.024), and older age at surgery (coefficient= -1.1830, p = 0.007) were independent predictors of low total QoL scores. Physical scores were independently associated with CMS (coefficient= -27.4815.31, p = 0.005), VP shunt placement (coefficient= -12.86, p = 0.025), and radiotherapy (coefficient=-13.62, p = 0.007). Emotional score was negatively associated with age at surgery (coefficient= -1.92, p = 0.0337) and chemotherapy (coefficient= -9.11, p = 0.003). Social scores were negatively associated with male sex (coefficient= -13.68, p = 0.001) and VP shunt placement (coefficient= -1.36, p = 0.005), whereas academic scores were negatively correlated with chemotherapy (coefficient= -17.45, p < 0.001) and age at surgery (coefficient= -1.92, p = 0.002). Extent of resection (coefficient=13.16, p = 0.021) was a good predictor of higher academic scores. Conclusions CMS results in long-term neurological and neuropsychological deficits, negatively affecting QoL, warranting early rehabilitation.